2019
DOI: 10.1038/s41467-019-08687-z
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate formation in salt dome cap rocks by microbial anaerobic oxidation of methane

Abstract: Major hydrocarbon accumulations occur in traps associated with salt domes. Whereas some of these hydrocarbons remain to be extracted for economic use, significant amounts have degraded in the subsurface, yielding mineral precipitates as byproducts. Salt domes of the Gulf of Mexico Basin typically exhibit extensive deposits of carbonate that form as cap rock atop salt structures. Despite previous efforts to model cap rock formation, the details of subsurface reactions (including the role of microorganisms) rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 60 publications
(90 reference statements)
0
21
0
Order By: Relevance
“…The anaerobic medium was prepared as previously described 75 in an anaerobic glove box (Xinmiao YQX-11, Shanghai, China). Given that in situ methane could be utilized by microbes 76 and therefore possibly influence methane production in the original reservoir environment, methane was initially added in the headspace of all the bottles at a ratio of 3 volumes CH 4 to 2 volumes N 2 (V/V; 1×10 5 Pa) in most bottles (except the bottles adding H 2 + CO 2 ). To determine the methane production potential, available methanogenic substrates were provided with acetate (50 mM), methanol (50 mM), H 2 + CO 2 (CH 4 / H 2 + CO 2 / N 2 , 3/1/2, V/V/V; 1 ×10 5 Pa), or sodium molybdate (28 mM), a specific inhibitor of sulfate reduction 77 .…”
Section: Methodsmentioning
confidence: 99%
“…The anaerobic medium was prepared as previously described 75 in an anaerobic glove box (Xinmiao YQX-11, Shanghai, China). Given that in situ methane could be utilized by microbes 76 and therefore possibly influence methane production in the original reservoir environment, methane was initially added in the headspace of all the bottles at a ratio of 3 volumes CH 4 to 2 volumes N 2 (V/V; 1×10 5 Pa) in most bottles (except the bottles adding H 2 + CO 2 ). To determine the methane production potential, available methanogenic substrates were provided with acetate (50 mM), methanol (50 mM), H 2 + CO 2 (CH 4 / H 2 + CO 2 / N 2 , 3/1/2, V/V/V; 1 ×10 5 Pa), or sodium molybdate (28 mM), a specific inhibitor of sulfate reduction 77 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Caesar et al (2019) showed the potential of MICP in mitigation of methane release into the atmosphere due to anaerobic methane oxidation. However, there are no studies on the use of this mechanism in bioconcrete yet.…”
Section: Methane Oxidationmentioning
confidence: 99%
“…Hence, the combination of IODP and non-IODP sediment core data used here, based on Egger et al (2018), can provide better constraints to the global DIC cycling at diffusive methane flux settings. Recently, it was postulated that carbonate cap rocks sealing the majority of hydrocarbon systems could be formed via AOM (Caesar et al, 2019). Further, carbonate authigenesis is suggested to be more dominant in slope settings, especially during the periods of widespread anoxia in geologic history, because of the prevalent anaerobic respiration in comparison to margins (Higgins et al, 2009;Schrag et al, 2013).…”
Section: Importance Of Methane Derived Authigenic Carbonate Precipitamentioning
confidence: 99%